Venus, Mars and the Sun : gender differences in the persuasive efficacy of GIFs with positive and negative emotional valence on promoting sunscreen use - Lee, Bianca Ann (2019)
Guided by the Limited Capacity Model of Motivated Mediated Message Processing (LC4MP), this study explored the persuasive efficacy of Graphics Interchange Formats (GIFs) and the moderating effect of gender on visual format and emotional valence. We conducted a 2 (visual format) x 2 (emotional valence) x 3 (message repetition) between- within subjects mixed design to examine the persuasiveness of messages promoting sunscreen use. Key findings were: (a) men were more persuaded by animated GIFs (vs. static graphics), (b) women were more persuaded by negative valence (vs. positive), (c) for animated GIFs, there was no significant difference in persuasion between positive and negative valence for both men and women, whereas for static graphics, men were more persuaded by positive valence and women by negative, and (d) within negative valence, men were more persuaded by animated GIFs (vs. static graphics) and women by static graphics (vs. animated GIFs). This paper contributes to LC4MP literature by exploring the use of GIFs in health communications, and gender as a moderator of visual format and valence. It discusses theoretical and practical implications of our findings, detailing the use of GIFs as a persuasion tool, and the best practices to tailor gender-specific health messages using visual format and valence.